Perfil De Aptitud Física De Las Capacidades Físicas Condicionales, En Los Jóvenes Entre Los 6 A 16 Años De Edad Adscritos A La Policía Cívica Juvenil (Pcj) De La Cuidad De Armenia Quindío (2014)
The purpose of this research is expressed in the title: Physical Fitness Profile of Conditional Physical Capabilities in Youths between 6 and 16 years of age assigned to the Juvenile Civic Police (PCJ) of the city of Armenia Quindío, where 56% of the population corresponds to the masculine gender, and 44% to the feminine gender, the approach was applied (Explanatory-Quantitative), in a descriptive and cross-sectional study. Where the objective was: To characterize the profile of physical fitness in the young people between 6 and 16 years of age assigned to the Juvenile Civic Police (PCJ) of the city of Armenia Quindío. The target population of 180 young boys and girls, assigned to the PCJ, was evaluated. Functional tests were used for conditional capacities and anthropometric measurements. Subsequently the information was entered in Excel XP-2010 where we calculated averages, standard deviation (DS) and percentiles. The instruments that were used to apply each of the tests were the application protocol of the Eurofit Battery; According to the results obtained in the investigation, the general evaluation determined that children between the ages of 6 and 16 ascribed to the Juvenile Civic Police (CCP) have strengths in some variables evaluated and in the same way, weaknesses that must Be analyzed in order to improve processes at the fitness level. It is essential to know the systems and methods of development of the physical condition in order to properly implement activities related to the improvement of basic physical abilities and the development of motor skills. The importance of this study is to provide data of interest to young people in the JCP, since they can continue to improve the process of training each of the conditional physical abilities and their future benefits.